Interactions of Man and His Environment - Jennings, Burgess H. author. aut Link
XII, 168 p.
Keywords: This symposium was a joint effort, co-sponsored by Northwestern University and Borg-Warner Corporation and included representatives of the latter-day estates of univerSity, industry, and government. All of these groups were deeply interested in participating, since the problems of man and his environment, especially his urban environ ment, are ones which can be solved only through a cooperative effort. The symposium proceedings present a review of the present position of man and his environment and outline the physical and social-science efforts being made to solve the problems posed by man's rapidly changing environment. The format of this book is such that Dr. Luther L. Terry's speech, "Environmental Health: Every body's Business," serves as an introduction to the many-faceted dis cussions on the interactions of man and his environment. Mr. P. B. Gordon's speech "Man and His Environment - Where Are We? Where Are We Going"?" aptly summarizes this symposium and serves this purpose in this publication. Every effort was exerted to make this symposium a general dis cussion meeting where contributions from both the formal speakers and the audience were received. The records of two panel discussions, including comments from the floor and replies by the speakers, are included in this volume. This publication is the result of the coordinated efforts of many contributors: the speakers, Northwestern University, Borg-Warner Corporation, the Symposium Planning Committee consisting of D. W.